27=d-18

Simple and best practice solution for 27=d-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=d-18 equation:


Simplifying
27 = d + -18

Reorder the terms:
27 = -18 + d

Solving
27 = -18 + d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
27 + -1d = -18 + d + -1d

Combine like terms: d + -1d = 0
27 + -1d = -18 + 0
27 + -1d = -18

Add '-27' to each side of the equation.
27 + -27 + -1d = -18 + -27

Combine like terms: 27 + -27 = 0
0 + -1d = -18 + -27
-1d = -18 + -27

Combine like terms: -18 + -27 = -45
-1d = -45

Divide each side by '-1'.
d = 45

Simplifying
d = 45

See similar equations:

| .83x-.16=4 | | x/4=10 | | 3w+2=w+7 | | 25x=-625 | | 2x^4=-250x | | 3(r+2)=-1(2r-4) | | 3*(-4)= | | x^2-5=157 | | x^2+x^2=12 | | (-3)*4= | | 16-8x-12=24+20 | | (-2)*(-8)= | | 9-4x+7x+15= | | 9x+17-7x+17=2 | | -5=-15 | | 7x+10=9x-4 | | (3x^2+5x-1)+(x^2-2x-7)=0 | | 6x-x-2x+8=7x | | 2(6x+2x)=2(x*x+12) | | -9.79(27x-65)=78.24(6x+34) | | 3x(x-5)-3x*3*3=-30 | | 5(x-6)-x=0 | | 2x*x+3x=3 | | 2xx+3x=3 | | -(2x-7)=4 | | ln(30)+ln(x)=24ln(x+1) | | x+4=4x-10 | | 1.5p=-0.3 | | 2.2+p=1 | | 2y+3=5 | | z^2-8iz-16=0 | | 7c-3c=2c+24 |

Equations solver categories